Evaluation of Local Food Processing Training Design Based on ADDIE AND FAO Food Security Pillars in Central Java - Agus Subhan Prasetyo; Gary Briers; Darlene Locke; Michael Shehane; Kim E. Dooley (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Food security is a strategic issue in Indonesia; however, evaluations of training programs supporting food security rarely systematically assess program design quality. This study analyzes the design of the Local Food Diversification Processing Training Program and evaluates its alignment with the Analysis and Design phases of the ADDIE model and the FAO’s Four Pillars of Food Security. A qualitative approach was employed, using content analysis of program reports and training materials prepared in 2024 by the Central Java Provincial Food Security Agency and its technical partners. The results indicate that the program design considered local food potential, participant characteristics, and objectives related to food processing skills and entrepreneurship development. Conceptually, the program design aligns with the FAO’s Four Pillars of Food Security. However, the needs analysis lacked standardized instruments, and learning outcome indicators had not been formulated in operational terms. These findings suggest that while the program has a strong substantive foundation, strengthening the Analysis and Design phases is necessary to enable more systematic measurement of its contribution to food security. The study confirms that the ADDIE model and the FAO’s Four Pillars can serve as an evaluation framework for assessing the design quality of food security-oriented training programs.